Exploring The Impact Of Micro, Small And Medium Enterprises (MSMEs) On Increasing Export Volume - Julij Ricky Nicholas (Dynamics Social : International Journal of Social Sciences and Communication, 2025)
This study aims to investigate the impact of Micro, Small and Medium Enterprises (MSMEs) on increasing export volumes in an economic context. This research was carried out by analyzing the contribution made by MSMEs to a country's exports, as well as the factors that influence the level of exports produced by the MSME sector. Data analysis methods include collecting secondary data from various trusted sources and regression analysis to measure the relationship between the variables involved in this research. It is hoped that the results of this research will provide better insight into the important role of MSMEs in increasing a country's exports.